SHARIA COMPLIANCE AND ISLAMIC CORPORATE GOVERNANCE - Aris Biyantoro; Nunung Ghoniyah (TRIKONOMIKA, 2019)
This study aims to examine the effect of sharia compliance and Islamic corporate governance on fraud in Sharia banks. Independent variables used are sharia compliance with Profit Sharing Ratio as a proxy and Islamic corporate governance. The dependent variable used is fraud. The population in this study is all Sharia Banks which is registered in Bank Indonesia in the period 2015 to 2017. The sample was selected using purposive sampling method. Sample size in this research as much as 33 Sharia Banks. Those total samples used in this study which consist of 11 Sharia Banks within 3-year study period. The analytical method used in this study is multiple linier regression.The results of this study indicate that the sharia compliance with the Profit Sharing Ratio as a proxy, has a negative effect on fraud in Sharia bank while Islamic corporate governance has no positive effect on fraud in Sharia banks.